On the nature of wind-forced upwelling and downwelling in Mackenzie Canyon, Beaufort Sea. (November 2021) - Lin, Peigen; Pickart, Robert S.; Fissel, David B.; Borg, Keath; Melling, Humfrey; Wiese, Francis K.
Highlights: Upwelling and downwelling occur both on the shelf and within Mackenzie Canyon. Coastal upwelling/downwelling is driven by the local wind stress. Canyon upwelling/downwelling is associated with wind stress curl in the Canada Basin. Atlantic Water can be fluxed onto the shelf when both coastal/canyon upwelling occur. Dense winter water can be fluxed offshore when both coastal/canyon downwelling occur. Abstract: Data from a four-mooring array deployed across the shelf and slope of Mackenzie Canyon, from 2016 to 2018, are used to characterize wind-driven upwelling and downwelling events and investigate their impact on the transport of water masses. We distinguish between coastal upwelling/downwelling forced by the along-coast wind stress, and canyon upwelling/downwelling associated with the wind stress curl in the Canada Basin. During coastal upwelling (downwelling), the isopycnals slope upward (downward) above the shelf bathymetry, and the normally westward-flowing shelf current is strengthened (reversed). During canyon upwelling (downwelling), the isopycnals slope upward (downward) progressing onshore relative to the background condition, and the cyclonic recirculation in the canyon is stronger (weaker), with an up-canyon (down-canyon) component on the upper slope. During periods of simultaneous coastal and canyon upwelling, Atlantic Water from the basin can be fluxed onto the shelf. These occurrences are dictated by the combination of three factors: the coastal upwelling strength, canyon upwelling strength, and the background depth of the offshore Pacific Water-Atlantic Water interface. Dense winter water is formed on the shelf by enhanced air-sea buoyancy flux during freeze-up and subsequent openings in the ice. During simultaneous coastal and canyon downwelling this water be fluxed offshore into the canyon, with the potential to ventilate the interior halocline.